A decade of dedication: Giving, giving, giving… and giving up teaching - Mulholland, Judith; Wallace, John (Canadian Journal of Education/Revue canadienne de l'éducation, 2013)
A decade of dedication: Giving, giving, giving… and giving up teaching Abstract In this paper we explore the circumstances leading to an elementary teacher’s decision to leave the profession. We analyse her narratives of eleven years of teaching using a storyline technique and a framework provided by the five aspects of teacher self-understandings (Kelchtermans, 2009) and the interplay between vulnerability, micro-political literacy and self-understanding. We suggest that, particular types of job perception predispose teachers to high levels of vulnerability. We suggest that teachers need, well as developing micro political literacy, to consider reaching an understanding of their personal giving capacity in teaching contexts, in order to manage vulnerability and negative impact of self understanding. Dix ans de dévouement : don de soi et abandon de l’enseignement Dans cet article nous analysons les circonstances qui ont conduit une enseignante de niveau élémentaire à abandonner l’enseignement. Nous analysons les récits dans lesquels elle raconte ses onze années d’enseignement, au moyen d’une technique de récit et d’un cadre donné par les cinq aspects de la compréhension de soi chez les enseignants (Kelchtermans, 2009), et nous nous penchons également sur l’interaction entre la vulnérabilité, les connaissances micro-politiques et la compréhension de soi. Nous croyons que certains types de perception de leur travail prédisposent les enseignants à une plus grande vulnérabilité. Outre les connaissances micro-politiques, les enseignants doivent développer une meilleure compréhension de leur capacité personnelle de se donner en contexte d’enseignement, afin de gérer leur vulnérabilité et l’impact négatif de la compréhension de soi.